2021
DOI: 10.3389/fenrg.2021.653542
|View full text |Cite
|
Sign up to set email alerts
|

Electrode and Electrolyte Materials From Atomistic Simulations: Properties of LixFEPO4 Electrode and Zircon-Based Ionic Conductors

Abstract: LixFePO4 orthophosphates and fluorite- and pyrochlore-type zirconate materials are widely considered as functional compounds in energy storage devices, either as electrode or solid state electrolyte. These ceramic materials show enhanced cation exchange and anion conductivity properties that makes them attractive for various energy applications. In this contribution we discuss thermodynamic properties of LixFePO4 and yttria-stabilized zirconia compounds, including formation enthalpies, stability, and solubilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 104 publications
(224 reference statements)
1
19
0
Order By: Relevance
“…However, different applied approximations (e.g., exchange-correlation functionals) result in different quality of the computed structural data ( Perdew et al, 2008 ; Blanca-Romero et al, 2014 ). In a series of papers on orthophosphates we demonstrated that a very good match to the structural parameters, especially the Ln -O bond lengths, can be obtained with the PBEsol exchange-correlation functional ( Perdew et al, 2008 ) and the DFT + U method with the Hubbard U parameter derived from first principles ( Blanca-Romero et al, 2014 ; Beridze et al, 2016 ; Kowalski et al, 2021 ). Finkeldei et al (2017) have shown that PBEsol functional can predict accurate value of the lattice parameter of the Nd 2 Zr 2 O 7 pyrochlore.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, different applied approximations (e.g., exchange-correlation functionals) result in different quality of the computed structural data ( Perdew et al, 2008 ; Blanca-Romero et al, 2014 ). In a series of papers on orthophosphates we demonstrated that a very good match to the structural parameters, especially the Ln -O bond lengths, can be obtained with the PBEsol exchange-correlation functional ( Perdew et al, 2008 ) and the DFT + U method with the Hubbard U parameter derived from first principles ( Blanca-Romero et al, 2014 ; Beridze et al, 2016 ; Kowalski et al, 2021 ). Finkeldei et al (2017) have shown that PBEsol functional can predict accurate value of the lattice parameter of the Nd 2 Zr 2 O 7 pyrochlore.…”
Section: Resultsmentioning
confidence: 99%
“…The core electrons of atoms have been represented by the ultrasoft pseudopotentials (Vanderbilt, 1990), with the relevant planewave energy cutoff of 50 Ryd. Following our broad experience on computation of lanthanide orthophosphates and zirconates, and uranium-oxides (e.g., Beridze and Kowalski, 2014;Blanca-Romero et al, 2014;Li et al, 2015;Beridze et al, 2016;Kowalski et al, 2021) here we applied a parameter free DFT + U approach. In this method, the Hubbard U parameter values are computed from first principles using the linear response method of Cococcioni and de Gironcoli (2005).…”
Section: Computational Approachmentioning
confidence: 99%
See 3 more Smart Citations